Examination of the Physical Activity of Frail Community-dwelling Elderly Using a Triaxial Accelerometer - YANAGI, Hisako; YABUSHITA, Noriko; WAKAYAMA, Shuichi; NAKANO, Satoko; FUJITA, Yoshihiko; HOTTA, Kazushi; MAKI, Naoki (Rigaku ryoho kagaku, 2020)
[Purpose] The purpose of this study was to measure the physical activity of frail community-dwelling elderly using an accelerometer. [Participants and Methods] Thirty-two elderly persons (11 males and 21 females) who participated in a care prevention class were the subjects. The Mini Mental State Examination (MMSE), Life-Space Assessment (LSA), physical function (grip strength, 5 chair stand-ups, Timed Up and Go test (TUG), eyes open one leg standing time, 5-m maximum walking speed, and standing time from the long sitting position) and physical activity (PA) were evaluated, and standing, sitting, supine, sedentary behavior (SB), low, medium, and high intensity exercise times, and moderate-to-vigorous physical activity (MVPA) were measured using an accelerometer. [Results] Females showed significantly higher values for all physical function assessments except grip strength, significantly shorter sitting and SB times, and significantly longer exercise times in all intensity categories, and a negative correlation coefficient was found between their mobility ability including TUG and PA. [Conclusion] The results suggest that continuation of daily activities at home is necessary for maintaining physical function.